2017
DOI: 10.1038/s41526-017-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mk VI SkinSuit on skin microbiota of terrestrial volunteers and an International Space Station-bound astronaut

Abstract: Microgravity induces physiological deconditioning due to the absence of gravity loading, resulting in bone mineral density loss, atrophy of lower limb skeletal and postural muscles, and lengthening of the spine. SkinSuit is a lightweight compression suit designed to provide head-to-foot (axial) loading to counteract spinal elongation during spaceflight. As synthetic garments may impact negatively on the skin microbiome, we used 16S ribosomal RNA (rRNA) gene amplicon procedures to define bacterial skin communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Trunk muscle atrophy and reduced muscle tone ( McNamara et al, 2019 ) may contribute to inter-vertebral disc (IVD) pathology and contributes to an apparent increased risk of IVD herniation post-flight ( Johnston et al, 2010 ). Moderate axial loading via elasticated body suits has been suggested to promote core stability ( Rathinam et al, 2013 ) with some developed for μg environments ( Waldie and Newman, 2011 ) demonstrated to be compatible with aerobic ( Attias et al, 2017 ) and resistive ( Carvil et al, 2017 ) exercise on Earth, and on the ISS ( Stabler et al, 2017 ). However, whilst these suits may promote trunk muscle activation during exercise, such an approach is unlikely to mitigate multi-organ deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk muscle atrophy and reduced muscle tone ( McNamara et al, 2019 ) may contribute to inter-vertebral disc (IVD) pathology and contributes to an apparent increased risk of IVD herniation post-flight ( Johnston et al, 2010 ). Moderate axial loading via elasticated body suits has been suggested to promote core stability ( Rathinam et al, 2013 ) with some developed for μg environments ( Waldie and Newman, 2011 ) demonstrated to be compatible with aerobic ( Attias et al, 2017 ) and resistive ( Carvil et al, 2017 ) exercise on Earth, and on the ISS ( Stabler et al, 2017 ). However, whilst these suits may promote trunk muscle activation during exercise, such an approach is unlikely to mitigate multi-organ deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Apollo) did not find composition changes in the skin's bacteria [10]. Sugita et al found that lipophilic skin fungi predominated before, during, and after spaceflight, but they observed that a specific or uncommon microorganism (such as the ascomycetous yeast Cyberlindnera jadinii) might be able to proliferate in a closed environment like that onboard the ISS [11]. Additional studies are needed to further qualify the changes of the skin's microbiota during spaceflight and to aid in preventing infections related to these changes.…”
Section: Microbiotamentioning
confidence: 99%
“…Studies examining the colonization of the ISS found skin-associated genera on board, including Staphylococcus, Micrococcus, Bacillus, Streptococcus, and some potentially pathogenic fungi [11]. The Russian Mir has also been studied for colonization, with isolates from various organisms including Escherichia coli, Serratia marcescens, a presumed Legionella species, spirochetes, and dust mites [16].…”
Section: Infections In Space a Contributing Factors I Colonization And Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SkinSuit study, microgravity was employed directly in vivo ( Stabler et al., 2017 ). This study was performed to determine the effectiveness of a lightweight compression suit designed to provide head-to-foot loading to counteract spinal elongation during spaceflight.…”
Section: Esa-(co)funded Omics Workmentioning
confidence: 99%